The MULTINATIONAL ENTERPRISE : theory and history - Casson, Mark, 1945- (Edward Elgar Publishing Limited, 2018)
This book summarises Mark Casson's recent research on the multinational enterprise. This work is firmly rooted in history and examines the evolution of the internalisation theory of the multinational enterprise over the past forty years and, in the light of this, considers its potential for further development. The book also explores internationalisation theory in respect to marketing and brands, the supply chain, risk management as well as methodology.
Keywords: mezinárodní podnikání; nadnárodní společnosti; znalostní ekonomika; podniková ekonomika; international business; international business enterprises; knowledge economy; managerial economics; kolektivní monografie; elektronické knihy; collective monographs; electronic books